2017
DOI: 10.1186/s12936-017-1964-z
|View full text |Cite
|
Sign up to set email alerts
|

School-based diagnosis and treatment of malaria by teachers using rapid diagnostic tests and artemisinin-based combination therapy: experiences and perceptions of users and implementers of the Learner Treatment Kit, southern Malawi

Abstract: BackgroundTraining teachers to diagnose uncomplicated malaria using malaria rapid diagnostic tests and treat with artemisinin-based combination therapy has the potential to improve the access of primary school children (6–14 years) to prompt and efficient treatment for malaria, but little is known about the acceptability of such an intervention. This qualitative study explored experiences and perceptions of users and implementers of a programme of school-based malaria case management via a first-aid kit—the Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…This perception analysis demonstrated the LTK project's success in increasing accessibility to malaria diagnostics and treatment [16]. Students reported that they sought care more frequently when feeling unwell [16]. The intervention was associated with a reduction in school absences due to health issues and a reduction in students dropping out of school or repeating grades [17].…”
Section: Malaria Detection In Schoolsmentioning
confidence: 85%
See 4 more Smart Citations
“…This perception analysis demonstrated the LTK project's success in increasing accessibility to malaria diagnostics and treatment [16]. Students reported that they sought care more frequently when feeling unwell [16]. The intervention was associated with a reduction in school absences due to health issues and a reduction in students dropping out of school or repeating grades [17].…”
Section: Malaria Detection In Schoolsmentioning
confidence: 85%
“…The Learner Treatment Kit (LTK), funded by Save the Children and implemented in conjunction with the Malawi Ministries of Health and Education, the London School of Hygiene and Tropical Medicine, and the University of Malawi, demonstrates a social innovation in malaria diagnostics and treatment [16]. It uses schools as an entry point for care delivery, which both increases healthcare accessibility and incentivizes school attendance.…”
Section: Malaria Detection In Schoolsmentioning
confidence: 99%
See 3 more Smart Citations